Tocnost' dvizenij pri vzaimodejstvii s silami razlicnoj prirody - Nemcev, O. B. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The author studied dynamics of kinematic structure of the maximum fast exact movements with the amplitude 10 and 20 sm.